Gender and Development Included Forest Sector - ware, Rorisa midekso; Omer, Kemer (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The aim of this study is to analyze gender issues in development in Ethiopia, with a particular focus on the forest sector. This study seeks to identify the challenges and barriers to gender equality across key sectors such as education, employment, health, and political representation, while also assessing the government of Ethiopia's policies and legal frameworks related to gender. Methodology: The methodology employed in this study involves both quantitative and qualitative approaches, utilizing a literature review and secondary data analysis. Findings: Key findings indicate that, although Ethiopia has made significant progress in achieving gender equality, such as increased girls' enrollment in primary education, improved maternal health, and high political representation of women, there are still considerable disparities, particularly in the forest sector. Women face limitations in accessing forest resources and decision-making processes, despite their critical role in forest management. Additionally, the unpaid care work burden and limited access to education result in women being overrepresented in low-paid domestic work and less involved in politics and public life. Gender-blind policies remain a significant barrier to women's empowerment in the forest sector. Originality/value: This paper is original Paper type: a Research Paper